World Development Report 1982 : International Development Trends; Agriculture and Economic Development; World Development Indicators - World Bank (World Development Report, 1982)
This report reviews development prospects in the international economy and supplements the extensive discussion of adjustment issues in the 1981 World Development Report. It finds that, although international prospects have worsened over the past year, during the remainder of the decade the middle-income countries should be able to continue narrowing the income gap between themselves and the industrial countries. The prospects for many of the low-income countries, however, remain a matter of grave concern. The report concentrates on agriculture, which remains the chief source of income for close to two-thirds of the population in developing countries and for the vast majority of the world's poor. Informing the discussion is the experience gained by the World Bank in helping to finance some 800 agricultural and rural development projects in more than 70 countries - experience supported by its broad, intensive programs of economic, scientific, and social research. Numerous tables and multicolor maps and graphics supplement the main body of the report; case studies are interspersed to provide analyses directly related to the substance of the text. The final portion of the report comprises world development indicators, 25 two-page tables containing economic and social profiles of more than 120 countries